Polyacrylonitrile spinning solution and its preparation method and application

During the preparation of the polyacrylonitrile spinning solution, the polyacrylonitrile resin and sodium thiocyanate aqueous solution were dispersed and slurried and high-speed sheared, which solved the problem of low solid content and high viscosity of the stock solution, and achieved high efficiency preparation Performance PAN raw silk effect.

CN116065250BActive Publication Date: 2025-02-11CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202111275918.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-02-11
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

In the prior art, the solid content of the polyacrylonitrile spinning stock solution is low and the viscosity is high, which leads to difficulties in preparing high-performance PAN stock.

Method used

By mixing the polyacrylonitrile resin with a first aqueous solution of sodium thiocyanate at a temperature of 10 to 25°C, a slurry mixture was formed, and sheared with a high-temperature and high-concentrated sodium thiocyanate solution at 80 to 90°C, the preparation was performed Polyacrylonitrile spinning liquid with high solid content and low viscosity.

Benefits of technology

The solid content and viscosity of the polyacrylonitrile spinning stock solution are improved, the slurry viscosity is low and the fluidity is good. It is suitable for continuous production and can prepare high-quality polyacrylonitrile raw silk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003329970330000051
    Figure BDA0003329970330000051
  • Figure BDA0003329970330000061
    Figure BDA0003329970330000061
  • Figure BDA0003329970330000062
    Figure BDA0003329970330000062
Patent Text Reader

Abstract

The present invention relates to the field of textile chemicals and high-performance fiber technology, and specifically to a polyacrylonitrile spinning solution, a preparation method thereof, and an application thereof. The preparation method of the polyacrylonitrile spinning solution comprises the following steps: (1) mixing a polyacrylonitrile resin with a first sodium thiocyanate aqueous solution at a temperature of 10 to 25°C, and dispersing and beating at a temperature of 15 to 25°C to form a slurry mixture; (2) mixing the slurry mixture with a second sodium thiocyanate aqueous solution at a temperature of 100 to 140°C, and then high-speed shearing at a temperature of 80 to 90°C to obtain a polyacrylonitrile spinning solution; the polyacrylonitrile resin has a number average particle size of 2 to 9 um, a particle size distribution index of 1.5 to 2.8, and a sedimentation value of 3.0 to 4.2. According to the preparation method of the present invention, the slurry viscosity in the preparation process of the polyacrylonitrile spinning solution is low, the fluidity is good, and it can be used for continuous production, and the prepared polyacrylonitrile spinning solution has a high solid content, a low viscosity, and good extrusion uniformity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile chemicals and high-performance fibers, and in particular to a polyacrylonitrile spinning solution and a preparation method and application thereof. Background Art

[0002] Carbon fiber is widely used in aerospace, satellite rockets, automobile industry, wind power, sports and leisure products and other fields due to its high specific strength and modulus, good chemical stability, low thermal expansion coefficient and other properties, and the global demand is increasing year by year. Among the three organic fiber precursors, polyacrylonitrile is the one with the highest usage ratio and the best product quality. The development and application of carbon fiber is playing an increasingly important role in improving the national military strength and the competitiveness of industrial products. In the production process of carbon fiber, the performance of the precursor is the main factor restricting the performance of carbon fiber.

[0003] The commonly used polyacrylonitrile spinning solution includes N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide and sodium thiocyanate aqueous solution. Compared with other solvents, sodium thiocyanate aqueous solution is non-toxic and is an excellent solvent used in the polyacrylonitrile spinning process. However, when polyacrylonitrile is dissolved in sodium thiocyanate aqueous solution, gelation and other phenomena are prone to occur during the dissolution process, and the solubility is low. The prepared polyacrylonitrile spinning solution has high viscosity, which is an important factor restricting the preparation of high-performance PAN precursor. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low solid content and high viscosity of polyacrylonitrile spinning solution in the prior art, and to provide a polyacrylonitrile spinning solution and a preparation method and application thereof. The preparation method prepares polyacrylonitrile spinning solution with high solid content and low viscosity, and the slurry viscosity in the preparation process is low and the fluidity is good, and it can be used for continuous production.

[0005] In order to achieve the above object, the present invention provides a method for preparing a polyacrylonitrile spinning solution in a first aspect, the method comprising the following steps:

[0006] (1) mixing a polyacrylonitrile resin with a first sodium thiocyanate aqueous solution at a temperature of 10 to 25° C., and dispersing and beating the mixture at a temperature of 15 to 25° C. to form a slurry-like mixture;

[0007] (2) mixing the slurry mixture with a second sodium thiocyanate aqueous solution at 100 to 140° C. and then shearing at a high speed at a temperature of 80 to 90° C. to obtain a polyacrylonitrile spinning solution;

[0008] The polyacrylonitrile resin has a number average particle size of 2 to 9 μm, a particle size distribution index of 1.5 to 2.8, and a sedimentation value of 3.0 to 4.2.

[0009] A second aspect of the present invention provides a polyacrylonitrile spinning solution prepared by the preparation method of the present invention.

[0010] A third aspect of the present invention provides a use of the polyacrylonitrile spinning solution of the present invention in preparing polyacrylonitrile precursor.

[0011] The method for preparing polyacrylonitrile spinning stock solution of the present invention has the advantages of low viscosity, good fluidity and stable properties of the obtained slurry mixture; after the slurry mixture is mixed with a high-temperature and high-concentration sodium thiocyanate solution, the sodium thiocyanate solution can easily diffuse into the interior of polyacrylonitrile particles; the slurry viscosity is low and the fluidity is good in the process of preparing the polyacrylonitrile spinning stock solution, and the slurry can be used for continuous production; the prepared polyacrylonitrile spinning stock solution has high solid content and low viscosity, and the polyacrylonitrile spinning stock solution has good extrusion uniformity and stability. DETAILED DESCRIPTION

[0012] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0013] According to a first aspect of the present invention, the present invention provides a method for preparing a polyacrylonitrile spinning solution, the method comprising the following steps:

[0014] (1) mixing a polyacrylonitrile resin with a first sodium thiocyanate aqueous solution at a temperature of 10 to 25° C., and dispersing and beating the mixture at a temperature of 15 to 25° C. to form a slurry-like mixture;

[0015] (2) mixing the slurry mixture with a second sodium thiocyanate aqueous solution at 100 to 140° C. and then shearing at a high speed at a temperature of 80 to 90° C. to obtain a polyacrylonitrile spinning solution;

[0016] The polyacrylonitrile resin has a number average particle size of 2 to 9 μm, a particle size distribution index of 1.5 to 2.8, and a sedimentation value of 3.0 to 4.2.

[0017] According to a preferred embodiment of the present invention, the mass concentration of the first sodium thiocyanate aqueous solution is 30-35 wt %, preferably 31-34 wt %.

[0018] According to a preferred embodiment of the present invention, in the slurry mixture, the mass content of the polyacrylonitrile resin is 18 to 25 wt%, preferably 19 to 23 wt%.

[0019] According to a preferred embodiment of the present invention, based on the total weight of the polyacrylonitrile spinning solution, the mass content of the polyacrylonitrile resin is 10 to 13 wt%, preferably 11 to 12.5 wt%.

[0020] According to a preferred embodiment of the present invention, the mass concentration of the second sodium thiocyanate aqueous solution is 56-65wt%.

[0021] According to a preferred embodiment of the present invention, the mass ratio of the slurry mixture to the second sodium thiocyanate aqueous solution is 30-35 wt %.

[0022] According to the present invention, the present invention has no special requirements for the polyacrylonitrile, and all polyacrylonitrile with the above-mentioned properties in the art can be applied to the present invention. With respect to the present invention, the present invention provides a method for preparing polyacrylonitrile with the above-mentioned properties, which method comprises:

[0023] The acrylonitrile monomer, the first comonomer and the second comonomer are mixed in pure water, and a polymerization reaction is carried out under polymerization reaction conditions by a water-soluble initiator. After the reaction is completed, a polymerization reaction liquid is obtained, and the polymerization reaction liquid is stripped, washed with water, filtered, and dried to prepare a polyacrylonitrile resin.

[0024] In the present invention, the removal of monomers refers to the removal of unreacted monomers under vacuum conditions.

[0025] The present invention has no special requirements for the conditions of washing, filtering and drying of the polymerization reaction liquid. Conventional washing, filtering and drying conditions in the art are applicable to the polymer reaction liquid described in the present invention. Preferably, the polyacrylonitrile resin drying process is carried out under a nitrogen atmosphere at a temperature of 100-150°C, preferably under a nitrogen atmosphere at a temperature of 110-130°C.

[0026] According to a preferred embodiment of the present invention, based on the mass of the entire polymerization system, the total content of acrylonitrile monomer, the first comonomer and the second comonomer is 30 to 45 wt%, preferably 35 to 42 wt%.

[0027] According to a preferred embodiment of the present invention, based on the total weight of the monomers, the content of the first comonomer is 1-5 wt%, preferably 2-4 wt%.

[0028] According to a preferred embodiment of the present invention, based on the total weight of the monomers, the content of the second comonomer is 0.5 to 2.0 wt%, preferably 0.8 to 1.5 wt%.

[0029] According to a preferred embodiment of the present invention, the mass ratio of the water-soluble azo initiator to the total mass of the monomers is 0.2% to 0.7%:1, preferably 0.25% to 0.65%:1.

[0030] According to a preferred embodiment of the present invention, the polymerization conditions include: the reaction temperature is 60-80°C, preferably 65-75°C.

[0031] According to the present invention, the reaction time is reasonably adjusted according to the reaction temperature. Preferably, the polymerization reaction time is 60-100 min, more preferably 70-90 min.

[0032] According to a preferred embodiment of the present invention, the first comonomer is selected from at least one of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate and vinyl acetate.

[0033] According to a preferred embodiment of the present invention, the second comonomer is selected from at least one of methacrylic acid, acrylic acid, itaconic acid, acrylamide and methacrylamide.

[0034] According to a preferred embodiment of the present invention, the solid content of the polymerization reaction liquid is 25-42wt%, preferably 31-42wt%, and more preferably 35-42wt%.

[0035] According to a preferred embodiment of the present invention, the viscosity of the polymerization reaction liquid is 300-500cp.

[0036] According to a second aspect of the present invention, the present invention provides a polyacrylonitrile spinning solution prepared by the preparation method of the present invention.

[0037] According to a third aspect of the present invention, the present invention provides a use of the polyacrylonitrile spinning solution of the present invention in preparing polyacrylonitrile precursor.

[0038] The present invention will be described in detail below through examples.

[0039] Examples 1 to 10

[0040] The first and second comonomers are methyl acrylate and itaconic acid, respectively, and the mass ratio of acrylonitrile, methyl acrylate and itaconic acid is 96:3:1. Based on the weight of the entire polymerization system, the total amount of monomers added is shown in Table 1. The initiator is azobisisobutyramidine hydrochloride (AIBA), and the amount of initiator added is shown in Table 1 based on the total weight of acrylonitrile, methyl acrylate and itaconic acid. All monomers, initiators and pure water are introduced into a continuous stirring polymerization reactor, and polymerization reaction is carried out under polymerization conditions. The reaction temperature and time are shown in Table 1. After the reaction is completed, a polymerization reaction liquid is obtained, and the unreacted monomers in the polymerization reaction liquid are removed under vacuum, and then vacuum filtration and washing and drying at 120°C under a nitrogen atmosphere are performed to obtain polyacrylonitrile resin powder.

[0041] Comparative Examples 1 to 4

[0042] The first and second comonomers are methyl acrylate and itaconic acid, respectively, and the mass ratio of acrylonitrile, methyl acrylate and itaconic acid monomers is 96:3:1. Based on the weight of the entire polymerization system, the total amount of monomers added is shown in Table 1. The initiator uses sodium chlorate-sodium metabisulfite (oxidation-reduction system), and the amount of initiator added is shown in Table 1 based on the total weight of acrylonitrile, methyl acrylate and itaconic acid. The polymerization reaction time and temperature are shown in Table 1. After the reaction is completed, a polymerization reaction liquid is obtained, and the unreacted monomers in the polymerization reaction liquid are removed under vacuum. The resulting polymer is then vacuum filtered and washed and dried at 120°C under a nitrogen atmosphere to obtain a polyacrylonitrile resin powder with controllable particle size and uniform distribution.

[0043] Table 1 Raw material composition and polymerization conditions of Examples 1-10 and Comparative Examples 1-4

[0044]

[0045]

[0046] In order to examine the polymerization reaction of the embodiments and comparative examples, the solid content of the polymerization reaction liquid can be used to characterize the degree of reaction. The specific method is: take a certain mass of the polymerization reaction liquid, repeatedly filter and wash, remove monomers, initiators and other impurities, dry in a 60°C oven to constant weight, weigh the powder weight, and the solid content is the ratio of the powder weight to the polymerization reaction liquid weight; the viscosity of the reaction liquid can be used to characterize its fluidity. The specific method is: first stir the reaction liquid slurry evenly, use a rotational rheometer (DV-II-P type) to select an S63 rotor, a speed of 70RPM, and read the viscosity data 30s after turning it on. The specific test results are shown in Table 2.

[0047] Table 2 Properties of the polymerization reaction solution

[0048]

[0049]

[0050] In order to examine the molecular weight of the polymer products of the embodiments and comparative examples, the molecular weight and its distribution can be determined by gel permeation chromatography (GPC), and the specific method is: PMMA is used as the standard sample, 0.065 mol / LNaNO3 / DMF is used as the mobile sample, the flow rate is 1.5 ml / min, and the temperature is 40°C; in order to examine the size and distribution of polymer particles, the polymer particle size and distribution can be determined by a WQL particle analyzer, and the specific method is: the polymer sample is prepared into a 0.1-1.0% aqueous solution, ultrasonicated for 2 minutes, and then the particle size and distribution, including the number average particle size, weight average particle size and particle size distribution index, are determined by a particle analyzer; in order to examine the sedimentation behavior of polymer particles in water, the sedimentation value can be determined, and the specific method is: take the polymer sample to be analyzed, dry it, and then sieve it with an 85-mesh sample sieve, take 10 g of the sieved polymer, dilute it with water and transfer it into a 100 ml stoppered measuring cylinder, dilute it to 100 ml, then add a stopper and shake it to evenly, let it stand for 24 hours, and read the sedimentation volume. Sedimentation value = sedimentation volume / 10 (ml / g). The test results are shown in Table 3.

[0051] Table 3 Polymer molecular weight, particle size and sedimentation value

[0052]

[0053]

[0054] Examples 11 to 20

[0055] The polyacrylonitrile resin powder obtained in Examples 1 to 10 was mixed with a NaSCN aqueous solution at a temperature of 20°C and a concentration of 32.6wt%, the content of the polyacrylonitrile resin in the mixture was controlled to be 21wt%, the mixture material temperature was maintained at 20°C for dispersion and beating, and the polyacrylonitrile resin was uniformly dispersed in the NaSCN aqueous solution to form a slurry mixture; subsequently, the mixture was sent to a high-speed shearing machine together with a 140°C, 58% NaSCN aqueous solution, the mixture material temperature was maintained at 80°C, and the mixture was quickly dissolved under the rapid dispersion and grinding action of the high-speed shearing machine, and a coarse spinning solution was obtained. Based on the weight of the entire stock solution system, the resin content and the NaSCN content are shown in Table 4.

[0056] Embodiment 21

[0057] The polyacrylonitrile resin powder obtained in Example 8 was mixed with a NaSCN aqueous solution at a temperature of 11°C and a concentration of 35wt%, the content of the polyacrylonitrile resin in the mixture was controlled to be 25wt%, and the mixture material temperature was maintained at 11°C for dispersion and beating, so that the polyacrylonitrile resin was uniformly dispersed in the NaSCN aqueous solution to form a slurry mixture; subsequently, the mixture was sent to a high-speed shearing machine together with a 100°C, 60% NaSCN aqueous solution, the mixture material temperature was maintained at 90°C, and the mixture was quickly dissolved under the rapid dispersion and grinding action of the high-speed shearing machine, and a coarse spinning solution was obtained. Based on the weight of the entire stock solution system, the resin content and the NaSCN content are shown in Table 4.

[0058] Embodiment 22

[0059] The polyacrylonitrile resin powder obtained in Example 8 was mixed with a NaSCN aqueous solution at a temperature of 25°C and a concentration of 30wt%, the content of the polyacrylonitrile resin in the mixture was controlled to be 18wt%, and the mixture material temperature was maintained at 25°C for dispersion and beating, so that the polyacrylonitrile resin was uniformly dispersed in the NaSCN aqueous solution to form a slurry mixture; subsequently, the mixture was sent to a high-speed shearing machine together with a 120°C, 65% NaSCN aqueous solution, the mixture material temperature was maintained at 85°C, and the mixture was quickly dissolved under the rapid dispersion and grinding action of the high-speed shearing machine, and a coarse spinning solution was obtained. Based on the weight of the entire stock solution system, the resin content and the NaSCN content are shown in Table 4.

[0060] Comparative Examples 5 to 7

[0061] The polyacrylonitrile resin powder obtained in Comparative Examples 1 to 3 was used to prepare polyacrylonitrile spinning stock solutions according to the method of Examples 11 to 20. Based on the weight of the entire stock solution system, the resin content and NaSCN content are shown in Table 4. Based on the weight of the entire stock solution system, the resin content and NaSCN content are shown in Table 4.

[0062] Comparative Example 8

[0063] Different from Example 18, the polyacrylonitrile resin powder prepared in Example 8 was mixed with a NaSCN aqueous solution at a temperature of 10°C and a concentration of 50wt%, the content of the polyacrylonitrile resin in the mixture was controlled to be 12wt%, and the temperature of the mixture was maintained at 10°C for dispersion and pulping, so that the polyacrylonitrile resin was uniformly dispersed in the NaSCN aqueous solution to form a slurry mixture; the mixture was subsequently heated to 90°C and sent to a high-speed shearing machine, and quickly dissolved under the rapid dispersion and grinding action of the high-speed shearing machine, that is, a coarse spinning solution was obtained. Based on the weight of the entire stock solution system, the resin content and NaSCN content are shown in Table 4.

[0064] Comparative Example 9

[0065] Different from Example 18, the polyacrylonitrile resin powder prepared in Example 8 and a 140°C, 50% NaSCN aqueous solution were fed into a high-speed shearing machine according to the feed ratio in Table 4, and the mixture material temperature was maintained at 80°C. The mixture was quickly dissolved under the rapid dispersion and grinding action of the high-speed shearing machine to obtain a spinning solution. The resin content and NaSCN content are shown in Table 4 based on the weight of the entire solution system.

[0066] Table 4 Preparation conditions of polyacrylonitrile spinning solution

[0067]

[0068] In order to examine the slurry mixture of Examples 11-22 and Comparative Examples 5-9, the viscosity of the slurry mixture can be measured by a DV-II-P rotational rheometer. The specific method is: first, stir the slurry mixture evenly, select an S63 rotor with a rotation speed of 70RPM, and read the viscosity data 30 seconds after the rotation is turned on; the slurry mixture can be left to stand at a constant temperature of 25°C for 24 hours, and then the viscosity of the slurry mixture can be tested to compare the stability; the fluidity of the slurry mixture can be measured by taking about 50mL of the slurry in a 100mL beaker, stirring it evenly, and then pouring it at an angle of 60° to observe the slurry residue on the beaker wall. If all the mixture flows down, it means there is no wall adhesion; if a certain thickness of the mixture is deposited after it flows out, it means there is slight wall adhesion; if the deposition thickness increases with the outflow time, it means it is wall adhesion. The specific results are shown in Table 5.

[0069] Table 5 Viscosity, fluidity and stability of slurry mixture

[0070]

[0071] In order to examine the performance of the spinning solution of Examples 11-22 and Comparative Examples 5-9, the viscosity of the solution can be determined by a DV-II-P rotational rheometer. The specific method is: first, the spinning solution sample is placed in a constant temperature water bath at 54°C for 3 hours, an S63 rotor is selected, the rotation speed is 2.0RPM, and the viscosity is read when the rotation reading is stable; the uniformity and spinnability of the spinning solution can be determined by a constant temperature extrusion test. The specific method is: using a homemade spinning solution extrusion test device, a certain volume (600mL) of the solution is tested at a certain pressure (0.3MPa) and temperature (45°C), after passing through a filter equipped with a 400-mesh filter material, and then passing through an extrusion port with a pore size of 3mm, and then flowing down by its own weight, the average extrusion length, the extrusion quality within 1 minute and the number of breakages are tested, and the test results are shown in Table 6.

[0072] Table 6 Viscosity, uniformity and stability of spinning solution

[0073]

[0074] It can be seen from the results in Table 5 that, by using the present invention, the polyacrylonitrile resin is mixed with the first sodium thiocyanate aqueous solution at a temperature of 10 to 25° C., and then dispersed and slurried at 15 to 25° C., the resulting slurry mixture has good fluidity and stable properties.

[0075] It can be seen from the results in Table 6 that the slurry mixture prepared in Examples 11 to 22 is mixed with the second sodium thiocyanate aqueous solution at 100 to 140°C and then sheared at a high speed at a temperature of 80 to 90°C. The concentrated sodium thiocyanate solution easily diffuses into the interior of the particles, and the obtained polyacrylonitrile spinning stock solution is evenly dissolved, has few gel particles, low viscosity and good extrusion uniformity, and is suitable for preparing high-quality polyacrylonitrile precursor.

[0076] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing polyacrylonitrile spinning solution, characterized in that: The method comprises the following steps: (1) mixing polyacrylonitrile resin with a first sodium thiocyanate aqueous solution at a temperature of 10 to 25° C., and dispersing and beating at a temperature of 15 to 25° C. to form a slurry mixture; (2) mixing the slurry mixture with a second sodium thiocyanate aqueous solution at 100-140° C. and shearing at a high speed at a temperature of 80-90° C. to obtain a polyacrylonitrile spinning solution; The polyacrylonitrile resin has a number average particle size of 2 to 9 μm, a particle size distribution index of 1.5 to 2.8, and a sedimentation value of 3.0 to 4.2; The mass concentration of the first sodium thiocyanate aqueous solution is 31-35wt%; The mass concentration of the second sodium thiocyanate aqueous solution is 56-65wt%; The preparation method of the polyacrylonitrile resin comprises: The acrylonitrile monomer, the first comonomer and the second comonomer are mixed in pure water, and a polymerization reaction is carried out under polymerization reaction conditions by a water-soluble azo initiator. After the reaction is completed, a polymerization reaction liquid is obtained, and the polymerization reaction liquid is stripped, washed with water, filtered, and dried to prepare a polyacrylonitrile resin.

2. The preparation method according to claim 1, wherein In the slurry mixture, the mass content of polyacrylonitrile resin is 18-25wt%.

3. The preparation method according to claim 1 or 2, wherein Based on the total weight of the polyacrylonitrile spinning solution, the mass content of the polyacrylonitrile resin is 10-13wt%; and / or The mass ratio of the slurry mixture to the second sodium thiocyanate aqueous solution is 30-35wt%.

4. The preparation method according to claim 1, wherein Based on the mass of the entire polymerization system, the total content of acrylonitrile monomer, the first comonomer and the second comonomer is 30-45wt%; and / or Based on the total weight of the monomers, the first comonomer content is 1-5wt%; and / or Based on the total weight of the monomers, the content of the second comonomer is 0.5-2.0wt%; and / or The mass ratio of the water-soluble azo initiator to the total mass of the monomers is 0.2%-0.7%:

1.

5. The preparation method according to claim 4, wherein Based on the mass of the entire polymerization system, the total content of acrylonitrile monomer, the first comonomer and the second comonomer is 35-42wt%; and / or Based on the total weight of the monomers, the first comonomer content is 2-4wt%; and / or Based on the total weight of the monomers, the second comonomer content is 0.8-1.5wt%; and / or The mass ratio of the water-soluble azo initiator to the total mass of the monomers is 0.25% to 0.65%:

1.

6. The preparation method according to claim 1, wherein The polymerization conditions include: a reaction temperature of 60 to 80° C.; and / or The reaction time is 60-100min.

7. The preparation method according to claim 6, wherein: The polymerization conditions include: a reaction temperature of 65-75° C.; and / or The reaction time is 70-90min.

8. The preparation method according to claim 1, wherein The first comonomer is at least one selected from methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate and vinyl acetate; and / or The second comonomer is selected from at least one of methacrylic acid, acrylic acid, itaconic acid, acrylamide and methacrylamide.

9. The preparation method according to claim 1, wherein The solid content of the polymerization reaction liquid is 25-42wt%; and / or The viscosity of the polymerization reaction liquid is 300-500cp.

10. Polyacrylonitrile spinning solution prepared by the preparation method according to any one of claims 1 to 9.

11. Use of the polyacrylonitrile spinning solution according to claim 10 in preparing polyacrylonitrile precursor.

Citation Information

Patent Citations

  • Preparation method of polyacrylonitrile spinning solution used for carbon fibers

    CN109721677A

  • Preparation method of polyacrylonitrile resin with controllable particle size and uniform distribution

    CN112679654A

Cited By

  • Polyacrylonitrile spinning solution as well as preparation method and application thereof

    CN122483256A